2022
DOI: 10.1007/s11089-022-01005-3
|View full text |Cite
|
Sign up to set email alerts
|

‘Mad, bad, or possessed’? Perceptions of Self-Harm and Mental Illness in Evangelical Christian Communities

Abstract: Mental illness within evangelical Christian communities is frequently stigmatised, with many attributing it exclusively to demonic possession, lack of faith, personal sin, or other negative spiritual influences. This study explores perceptions of self-harm in the context of evangelical Christian faith communities using the novel qualitative story completion task. A convenience sample of 101 UK-based evangelical Christians completed a third-person fictional story stem featuring a devout female Christian who sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…In a social constructionist lens, stories are not framed as capturing any singular psychological reality but rather are believed to reflect a discursive or relativist reality ( Kitzinger and Powell, 1995 ; Burr, 2015 ). And in a contextualist epistemology, which lies somewhere between essentialist and social constructionist, stories are thought to reflect individual and social perceptions that are socially mediated and embedded ( Moller et al, 2021 ; Lloyd and Panagopoulos, 2022 ). This study adopts a contextualist epistemology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a social constructionist lens, stories are not framed as capturing any singular psychological reality but rather are believed to reflect a discursive or relativist reality ( Kitzinger and Powell, 1995 ; Burr, 2015 ). And in a contextualist epistemology, which lies somewhere between essentialist and social constructionist, stories are thought to reflect individual and social perceptions that are socially mediated and embedded ( Moller et al, 2021 ; Lloyd and Panagopoulos, 2022 ). This study adopts a contextualist epistemology.…”
Section: Methodsmentioning
confidence: 99%
“…For example, research has suggested that in some Christian circles mental ill-health may be understood as the outworking of one’s inner spiritual condition ( Webb, 2017 ). Indeed, there is some indication that for Evangelical Christians, discourse surrounding mental health may situate distress as emblematic of sin, demonic activity, or personal sinful behaviour ( Dein, 2020 ; Lloyd and Waller, 2020 ; Lloyd, 2021a ; Lloyd and Panagopoulos, 2022 ). With over 600 million global followers in which over 2 million are in the United Kingdom ( Pew Research Centre, 2015 ; Evangelical Alliance, 2020 ), evangelicalism can be thought of as a Protestant transdenominational movement, which places an emphasis on the literal interpretation of biblical texts; the need for a personal saving relationship with Jesus Christ; and the expectation of spiritual health and wellbeing for believers ( Bebbington, 1989 ; Stackhouse, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a group of critical social psychologists, Braun et al (2019), have developed formal guidelines for the use of SC in critical social psychology and qualitative research. As such, SC is currently undergoing renewed development as a methodology in qualitative psychology yet remains seldom explored in pastoral psychology, with only two publications using this method to date within the field of religion and spirituality (see Lloyd & Panagopoulos, 2022a;.…”
Section: The (Re)emergence Of Story Completion In Qualitative Studiesmentioning
confidence: 99%
“…This approach has the advantage of focusing on the micro level of participant perceptions about a given topic; however, it also enables researchers to explore the particular discourses participants draw upon to construct or make sense of certain phenomena through their narratives. Lloyd and Panagopoulos (2022a) used SC to explore social perceptions of self-harm within a large sample of evangelical Christians. Instead of asking participants outright about their experiences or views of self-harm, they were asked to respond to a gendered story cue in which a fictional devout Christian character, who had experienced some form of selfharm, visited their local church.…”
Section: Contextualist Story Completion Studiesmentioning
confidence: 99%
See 1 more Smart Citation